Забезпечення безпечних умов праці для профілактики професійних захворювань працівників металургійного і ливарного виробництва - Євтушенко, Наталія Сергіївна; Пономаренко, Ольга Іванівна; Твердохлєбова, Наталя Євгеніївна; Мезенцева, Ірина Олександрівна; Семенов, Євгеній Олександрович; Євтушенко, Степан Дмитрович (Фізико-технологічний інститут металів та сплавів Національної академії наук України, 2022)
У цій статті проведено комплексний аналіз умов праці працівників металургійного та ливарного виробництва, охарактеризовано основні причини нещасних випадків у ливарних цехах, проведено аналіз показників професійної захворюваності працівників у процесі лиття, сформульовано заходи щодо зменшення кількості нещасних випадків та виробничого травматизму, а також запропоновано рекомендації щодо усунення причин, що призводять до нещасних випадків та професійних захворювань працівників металургійних підприємств.

The successful functioning of domestic engineering enterprises, their high competitiveness is possible only on an advanced technological basis, including through the implementation of an innovative strategy in the field of labor protection, the success of which is determined by scientifically based planning of measures to prevent industrial injuries and occupational diseases. One of the most important industries in the field of mechanical engineering is the foundry. Modern foundry production is characterized by the following qualitative features: all branches of mechanical engineering in their technological process of manufacturing final products necessarily have castings as components. In the course of their work, foundry workers encounter harmful and hazardous production factors that adversely affect their safety and health, and, as a result, increase the likelihood of occupational diseases and injuries. Improving working conditions is the most important and priority task at the enterprise. The improvement of the state of labor protection, lowering the level of industrial injuries and occupational morbidity largely depends on the solution of this problem. An important aspect of which is the introduction of preventive measures to improve the safety of workers in foundries. These measures are of particular relevance. The development of these measures is possible only on the basis of information about the degree of danger of the influence of factors in the working environment and the labor process. This article carried out a comprehensive analysis of the working conditions of foundry workers, characterized the main causes of accidents in foundries, analyzed the indicators of occupational morbidity of workers in the casting process, formulated measures to reduce the number of accidents and industrial injuries, and also proposed recommendations to eliminate the causes, leading to accidents and occupational diseases of foundry workers.
Ensuring safe working conditions for the prevention of occupational diseases of workers in the metallurgical and foundry industries
Keywords: охорона праці; металургія; ливарне виробництво; виробничий травматизм; професійна захворюваність; умови праці; нещасний випадок; labor protection; metallurgy; foundry; industrial injuries; occupational morbidity; working conditions; accident